A modelization proposal for searching and recovering of information on computerized clinical records - José María Santamaría García; José Raúl Fernández del Castillo; Lourdes Jiménez Rodríguez; Jorge Luis Gómez González; Javier Pérez Rivas; León Gónzalez Sótos (Fundación para el Desarrollo de la Enfermería, 2005)
Nowadays, within the scenario of implementation of information systems, an interdisciplinary approach to analyse the clinical information recorded on computerized health documentation systems allow us to make a modelling proposal as a resource to discuss clinical cases. The proposed methodology is based on both the analyse of the clinical session structure as well as the use of web recovery skills. The endpoints are an information recovery model and standard searching formulas to documental comparison, being mandatory an operational development.